Localising livestock protein feed production and the impact on land use and greenhouse gas emissions. (18th July 2014) - Sasu-Boakye, Y.; Cederberg, C.; Wirsenius, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Livestock farmers in Sweden usually grow feed grains for livestock but import protein feed from outside Sweden. Aside from the economic implications, some environmental issues are associated with this practice. We used life cycle assessment to evaluate the impact of local protein feed production on land use and greenhouse gas emissions, compared with the use of imported protein feed, for pig meat and dairy milk produced in Sweden. Our results showed that local production reduced greenhouse gas emissions by 4.5% and 12%, respectively, for pigs and dairy cows. Land use for feed production in Sweden increased by 11% for pigs and 25% for dairy cows, but total land use decreased for pig production and increased for dairy milk production. Increased protein feed cultivation in Sweden decreased inputs needed for animal production and improved some ecological processes (e.g. nutrient recycling) of the farm systems. However, the differences in results between scenarios are relatively small and influenced to an extent by methodological choices such as co-product allocation. Moreover, it was difficult to assess the contribution of greenhouse emissions from land use change. The available accounting methods we applied did not adequately account for the potential land use changes and in some cases provided conflicting results. We conclude that local protein feed production presents an opportunity to reduce greenhouse gas emissions but at a cost of increasing land occupation in Sweden for feed production.